Autism Research: A Call for Collaboration - Britt Edwards; Genee Marks (New Zealand Journal of Teachers' Work)
This article introduces a PhD participatory action research project. A school-based approach that encourages positive social behaviour of children with autism is the key component of the research, where parents and educators join forces to problem-solve behaviour issues in the home. The behaviour intervention approach that is used offers a practical and naturalistic way of teaching students appropriate behaviour. Most importantly the approach has been developed by an educator who has autism so it is particularly insightful.